Neuroprotective Effects of Stem Cells in Ischemic Stroke - Weilin Xu; Jingwei Zheng; Liansheng Gao; Tao Li; Jianmin Zhang; Anwen Shao (Stem Cells International)
Ischemic stroke, the most common subtype of stroke, has been one of the leading causes of mobility and mortality worldwide. However, it is still lacking of efficient agents. Stem cell therapy, with its vigorous advantages, has attracted researchers around the world. Numerous experimental researches in animal models of stroke have demonstrated the promising efficacy in treating ischemic stroke. The underlying mechanism involved antiapoptosis, anti-inflammation, promotion of angiogenesis and neurogenesis, formation of new neural cells and neuronal circuitry, antioxidation, and blood-brain barrier (BBB) protection. This review would focus on the types and neuroprotective actions of stem cells and its potential mechanisms for ischemic stroke.